1992
DOI: 10.1111/j.1469-8137.1992.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NH3 and SO2 on the growth and competitive ability of Arnica montana L. and Viola canina L

Abstract: SUMMARYThe effects of atmospheric NH3 and SO, separately and in combination on the growth and competitive ability of three species of the Violion caninae alliance were investigated. Growth and nutrient concentrations of Viola canina and Arnica montana in mixed culture with Agrostis capillaris were examined in relation to that in monoculture. Seedlings were transplanted into heathland topsoil in pots and placed in open-top chambers for 9 months from autumn to summer, where they were exposed to ambient air, 90 /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Molinia caerulea , in particular, has been found to benefit from increased levels of N and may outcompete most other heathland species at high N availability (Aerts & Berendse 1988; Bobbink, Hornung & Roelofs 1998). Additionally, in experimental studies a range of the investigated rare species has been found to be more sensitive to high NH 4 concentrations or high NH 4 /NO 3 ratios (Dueck & Elderson 1992; De Graaf et al . 1998a; Van den Berg et al .…”
Section: Discussionmentioning
confidence: 99%
“…Molinia caerulea , in particular, has been found to benefit from increased levels of N and may outcompete most other heathland species at high N availability (Aerts & Berendse 1988; Bobbink, Hornung & Roelofs 1998). Additionally, in experimental studies a range of the investigated rare species has been found to be more sensitive to high NH 4 concentrations or high NH 4 /NO 3 ratios (Dueck & Elderson 1992; De Graaf et al . 1998a; Van den Berg et al .…”
Section: Discussionmentioning
confidence: 99%
“…Growth reductions in black spruce (Picea mariana) from ambient NO x and SO 2 exposure have been reported in association with Canadian smelter emissions (Aznar et al 2009), and injury to green leaves may occur from NO x concentrations of 300 μg m −3 (Bytnerowicz et al 1998) or lower when in the presence of SO 2 and O 3 (Nihlgard 1990). Pollutant mixtures have the potential to greatly increase the likelihood of injury to any plant species (Krupa and Legge 1999), and at concentrations below damage thresholds, air pollution may have invisible effects on plant species' biochemical functions, including growth, resistance to disease, or environmental stress (Bytnerowicz et al 1998;Nihlgard 1990), and competitive ability (Dueck and Elderson 1992). The UNECE-CLRTAP 24-h NO x threshold for boreal forest (Table 3) was also exceeded and is set to represent the protection of 95% of species at a 95% confidence level.…”
Section: Associated Impactsmentioning
confidence: 99%
“…Nitrogen oxides undergo photo-mediated reactions with volatile organic compounds (VOCs) forming tropospheric ozone (O 3 ) -capable of causing injury to natural and cultivated vegetation (Krupa and Kickert 1997;Krupa et al 1998;McLaughlin 1998), such as downwind of urban centres (Arbaugh et al 2003). In addition to these individual pathways, pollutant cooccurrence can intensify individual effects (Krupa and Legge 1999) and pollutant mixtures have been shown to cause injury to vegetation at levels below individual pollutant exposure thresholds (Dueck and Elderson 1992;Krupa and Legge 1999;Menser and Heggestad 1966).…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that other factors, such as increased habitat acidification and eutrophication, which are possibly negatively correlated with population size, influence the growth of A. montana as well (Dueck & Elderson 1992;Pegtel 1994;de Graaf et al 1998). It has been shown that other factors, such as increased habitat acidification and eutrophication, which are possibly negatively correlated with population size, influence the growth of A. montana as well (Dueck & Elderson 1992;Pegtel 1994;de Graaf et al 1998).…”
Section: Reproductive Success and Offspring Fitnessmentioning
confidence: 99%